FERICIRE ( BONHEUR ) – CONCEPTUALISATION ET LEXICALISATION À L`ÉPOQUE ROUMAINE PRÉ MODERNE - Gabriela STOICA (Diversitate si Identitate Culturala in Europa)
Fericire (happiness) – conceptualization and lexicalization in Early Modern Romanian. The paper deals with the conceptualization and lexicalization of the prototypical affect / fericire /[/ happiness /] during the Early Modern Romanian period ; based on a case study (Dinicu Golescu‘s text, Însemnarea călătoriii mele / Notes on my travel, 1824 - 1826, representative for the period in discussion), we shall analyse, from a contextual - semantic perspective, the words corresponding to the concept of happiness. These terms put forward a new conceptual - semantic dimension of happiness [Rom. fericire], culturally and historically justified (the orientation toward the Western values of the Enlightenment): happiness as moral ideal, as goal value. The concept is thus refined and the words (fericire, fericit) acquire new meanings that can be contextually decoded. The case of happiness is exponential for the general cultural, historical and linguistic mutations that emerge in the Romanian Principalities within the process of transition to modernity